Human Resource Development Strategies to Achieve Digital Transformation in Businesses - Sugiarto, Irwan (PT. LITERASI SAINS NUSANTARA, 2023)
Technological developments have created great opportunities, but also challenges in maintaining competitiveness and relevance. One of the main obstacles in achieving digital transformation is the lack of technological skills and knowledge among employees. This study aims to analyse HR development strategies to achieve digital transformation in business. This study involves a qualitative literature review approach, indicating that data will be scrutinised and explained by making use of information and texts gathered from diverse sources. The study results show that in order to achieve digital transformation in business, HR development strategy has proven to be an irreplaceable key element. In essence, companies should prioritise HR development that focuses on digital competencies, innovation, and a culture that supports change.